Trade and tradability: exports, imports, and factor markets in the Salter-Swan model - Thierfelder, Karen; Robinson, Sherman (Wiley, 2003)
We extend the Salter-Swan model to include both factor markets and semi-traded goods. In our model, changes in relative factor prices depend on changes in world commodity prices, factor endowments, and the trade balance. In contrast, only changes in world commodity prices can affect factor prices in the neoclassical trade model. The inclusion of semi-traded goods weakens the magnification effect of both the Stolper-Samuelson and Rybczynski theorems. When imports and domestic goods are poor substitutes, a characteristic of some commodities in developing countries, the sign of the Stolper-Samuelson effect is reversed.-- Authors' Abstract.